The Importance of Fulfilling Nutrition in Mothers Pregnancy at Talumelito Village - Harismayanti Harismayanti; Ani Retni; Fahmi A. Lihu (Journal of Universal Community Empowerment Provision, 2023)
The purpose of the counseling activity "The Importance of Fulfilling Nutrition for Mothers During Pregnancy in Talumelito Village" is to teach about fulfilling nutrition for pregnant women in Talumelito village, Telaga Biru sub-district. Balanced nutrition for pregnant and lactating mothers indicates that food consumption for pregnant and lactating women must meet the needs for themselves and for the growth and development of the fetus and baby. The method of activity carried out in this activity is percentages with the help of power points, leaflets, lectures and discussions with documentation, materials and attached attendance lists. This service activity can generally be carried out properly on January 16 in Talumelito Village, Telaga Biru District, Gorontalo Regency. This service was attended by 40 participants, both those who took part in counseling and those who took part in demonstrations. From the analysis of the results of the activity, it can be concluded that this community service activity ran smoothly and was of great interest to pregnant women in the village of Talumelito. Health information in counseling adds to the provision of knowledge for pregnant women and those who are planning a pregnancy.